2017
DOI: 10.1289/ehp242
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiles in Neonatal Mice following Oral Brominated Flame Retardant Exposures to Hexabromocyclododecane (HBCD) Alpha, Gamma, and Commercial Mixture

Abstract: Background:Hexabromocyclododecane (HBCD) is a high production volume brominated flame retardant added to building insulation foams, electronics, and textiles. HBCD is a commercial mixture (CM-HBCD) composed of three main stereoisomers: α-HBCD (10%), β-HBCD (10%), and γ-HBCD (80%). A shift from the dominant stereoisomer γ-HBCD to α-HBCD is detected in humans and wildlife.Objectives:Considering CM-HBCD has been implicated in neurodevelopment and endocrine disruption, with expected metabolism perturbations, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The doses used in this work are lower or in the range of previous studies carried out to examine the impact of TCDD, PhIP and B[ a ]P on the gut microbiota, allowing us to make comparisons and generate discussions 13 , 14 , 16 , 21 , 22 . The doses used for PAH, HBCD and deltamethrin exposures were far lower than those used for toxicity studies in mice 30 32 . The doses used in this study are still higher than the expected daily consumption.…”
Section: Discussionmentioning
confidence: 98%
“…The doses used in this work are lower or in the range of previous studies carried out to examine the impact of TCDD, PhIP and B[ a ]P on the gut microbiota, allowing us to make comparisons and generate discussions 13 , 14 , 16 , 21 , 22 . The doses used for PAH, HBCD and deltamethrin exposures were far lower than those used for toxicity studies in mice 30 32 . The doses used in this study are still higher than the expected daily consumption.…”
Section: Discussionmentioning
confidence: 98%
“…The predominance of α-HBCD in biota samples is probably related to the selective metabolism or biotransformation of the three isomers [62]. For instance, Szabo et al [63] observed in mice the bio-isomerization of γ-HBCD to α-HBCD; in addition, in vitro experiments showed a faster rate of biotransformation of βand γ-HBCD than α-HBCD [64]. It is also plausible that physicochemical differences among the HBCD molecules can contribute to the mentioned pattern: α-HBCD has a relatively higher water solubility than γand β-HBCD, which may result in some preferential uptake of this isomer in the aquatic environment [65].…”
Section: Discussionmentioning
confidence: 99%
“…The authors described that the use of metabolomics is an important and useful approach when we want to study the effect of a compound on the body to help identify biomarkers. [ 96 ]…”
Section: Studies In Animal Modelsmentioning
confidence: 99%